ETIKA PENGGUNAAN MEDIA SOSIAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Harif Rahman Suyatno; Martin Kustati; Bashori; Dipalpa Rego (JIP: Jurnal Ilmu Pendidikan, 2025)
The development of digital technology has encouraged the use of social media as a learning tool, including in Islamic Religious Education (PAI). However, the use of social media requires not only technical skills but also ethical literacy to ensure that learning interactions align with moral values and Islamic teachings. This study aims to analyze the implementation of ethical practices in social media use within PAI learning by examining the ethical literacy gap among students across various platforms such as Telegram, Discord, Threads, and LinkedIn Edu. Using a qualitative method with a case study approach, data were collected through interviews, observations, and documentation of digital learning activities. The findings reveal that although social media has been utilized for discussion and collaboration, there remains a low level of ethical awareness, such as impolite communication, inappropriate language use, and plagiarism. These findings emphasize the importance of integrating digital ethical literacy to ensure that PAI learning is effective, productive, and grounded in Islamic values, while also strengthening the role of educators as facilitators of digital ethics in the era of social media based learning